Automation in calculating stress-strain state of general-purpose welded structures in the programm Salome_Meca - Mikhail V. Zhukavets (Известия Томского политехнического университета: Промышленная кибернетика, 2025)
The paper demonstrates the principles of automation of engineering technology for calculating the stress-strain state of general-purpose welded structures using the YACS module (Salome_Meca software environment) – a tool for automating modeling using calculation schemes. This technology can be used by design bureaus to quickly determine optimal welded joints, since this technology, unlike the thermomechanical problem, is less resource-intensive and allows for faster determination of the stress-strain state of welded structures, thereby reducing design time.